Influencia de arcilla expandida en diseño de mezcla de concreto liviano alto rendimiento en distrito de Lircay Angaraes-Huancavelica - Obregon, Miguel (2022)
The influence of incorporating expanded clay in the mix design and strength of high-performance lightweight concrete in the District of Lircay - Angaraes - Huancavelica, to this effect, the question of our research is the following: How does the incorporation of clay influence expanded in the resistance of high-performance lightweight concrete in the District of Lircay - Angaraes - Huancavelica?, The influence of incorporating expanded clay in percentages of 5%, 10%, 15% and 20%, in the mix design significantly influences the resistance of high-performance lightweight concrete, workability and homogeneity are maintained as the clay is increased. expanded obtaining a settlement of 6 to 2.5 cm. within the limits of a balanced consistency. From the results obtained at 28 days of age of f'c=210 kg/cm² and f'c=280 kg/cm², it is concluded that the concretes with the addition of Clay in their different proportions are inferior to the standard concrete, surpassing the required resistance f'c=210 kg/cm² and f'c=280 kg/cm². With respect to the unit weight of fresh concrete for f'c=210kg/cm2 and f'c=280kg/cm2, it follows that its weight varied significantly in a minimal amount. It can be concluded that expanded clay is applicable for the production of concrete due to its resistance and lightness, being able to reduce the loads on structures such as slabs and walls. It can also be applied in fillings for pipe installations, reducing the proportions and the loads on them.